RETRACTED: The influence of age, gender and creativity of profession on manipulation behavior of young people - Mudrak Sofia (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001